Developing Force Fields from the Microscopic Structure of Solutions - Ploetz, Elizabeth A. (2010)
We have been developing force fields designed for the eventual simulation of peptides and proteins using the Kirkwood-Buff (KB) theory of solutions as a guide. KB theory provides exact information on the relative distributions for each species present in solution. This information can also be obtained from computer simulations. Hence, one can use KB theory to help test and modify the parameters commonly used in biomolecular studies. A series of small molecule force fields representative of the fragments found in peptides and proteins have been developed. Since this approach is guided by the KB theory, our results provide a reasonable balance in the interactions between self-association of solutes and solute solvation. Here, we present our progress to date. In addition, our investigations have provided a wealth of data concerning the properties of solution mixtures, which is also summarized. Specific examples of the properties of aromatic (benzene, phenol, p-cresol) and sulfur compounds (methanethiol, dimethylsulfide, dimethyldisulfide) and their mixtures with methanol or toluene are provided as an illustration of this kind of approach.